2022
DOI: 10.1101/2022.03.18.484943
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Low-Toxin Clostridioides difficile RT027 Strains Exhibit Robust Virulence

Abstract: Clostridioides difficile is a leading cause of healthcare-associated infections worldwide. Currently, there is lack of consensus on a single optimal diagnostic method for C. difficile infection (CDI). Nucleic acid amplification tests (NAAT) that detect toxin genes are highly sensitive, but their specificity limitations could inflate CDI rates. Alternate multi-step diagnostic algorithms emphasize the detection of C. difficile toxins TcdA/TcdB, and are premised on the rationale that stool toxin-negative (Tox-) C… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…GDH+ stool specimens may be negative for the toxin EIA test either because they harbor non-toxigenic C. difficile strains, or because the amount of toxin in the stool sample is below the threshold of detection in the clinical test. We have demonstrated that C. difficile isolated from a subset of the latter group also produce lower levels of toxin during in vitro culture and also in the rodent intestine, relative to ribotype-matched isolates from GDH + Toxin+ specimens (16). Nevertheless, such low-toxin C. difficile strains exhibited comparable virulence to high-toxin strains in a hamster model of acute CDI (16).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…GDH+ stool specimens may be negative for the toxin EIA test either because they harbor non-toxigenic C. difficile strains, or because the amount of toxin in the stool sample is below the threshold of detection in the clinical test. We have demonstrated that C. difficile isolated from a subset of the latter group also produce lower levels of toxin during in vitro culture and also in the rodent intestine, relative to ribotype-matched isolates from GDH + Toxin+ specimens (16). Nevertheless, such low-toxin C. difficile strains exhibited comparable virulence to high-toxin strains in a hamster model of acute CDI (16).…”
Section: Discussionmentioning
confidence: 88%
“…We have demonstrated that C. difficile isolated from a subset of the latter group also produce lower levels of toxin during in vitro culture and also in the rodent intestine, relative to ribotype-matched isolates from GDH + Toxin+ specimens (16). Nevertheless, such low-toxin C. difficile strains exhibited comparable virulence to high-toxin strains in a hamster model of acute CDI (16).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations